One Week of Low or Moderate Doses of Caffeinated Coffee Consumption Does Not Induce Tolerance to The Accute Effects of Caffeine on Sprint Performance - Raci Karayigit; Dicle Aras (Asociación Española de Ciencias del Deporte, 2021)
Habituation to acute performance responses of caffeine intake is still an ongoing debate. The aim of this study was to evaluate the effects of acute and 1 week consumption of caffeinated coffee on intermittent sprint cycling performance (12x4s with 90s active recovery) (ISP). Twenty four male team-sport players randomly divided into 3 groups (8 athletes for each): 0.16 gr/kg decaffeinated coffee ingestion in a day for 1 week (PLAGROUP), 0.08 caffeinated + 0.08 decaffeinated coffee (providing 3 mg/kg caffeine) (0.16 gr/kg in total) (LOWGROUP) and 0.16 gr/kg caffeinated coffee (providing 6 mg/kg caffeine) (MODGROUP). Participants underwent three test session: At the first two test sessions, ISP test was performed with acute ingestion of decaffeinated coffee (PLA) or 6 mg/kg of caffeine provided by coffee (FIRSTCAF) to test acute effects of caffeine intake. At the third test session, following to 1 week of coffee consumption, to test if tolerance develops, ISP was performed with ingestion 6 mg/kg of caffeine provided by coffee (SECONDCAF). A 2-way repeated measures ANOVA showed that although average peak (p=0,39; η2 =0,13) and average mean (p=0,11; η2 =0,15) power of total 12 sprints during ISP test were not statistically different between 1 week consumption groups, FIRSTCAF and SECONDCAF significantly increased peak power (p=0,01; η2 =0,44) and mean power (p=0,01; η2 =0,46) in the first three sprints compared to PLA in all consumption groups. It appears that no tolerance was developed in 1 week consumption of 3 or 6 mg/kg/day of caffeine provided by coffee.